Electromagnetic induction measurements with the vertically oriented dipole of the CMD Mini Explorer (71 cm transmitter-receiver spacing) taken in June 2024 in the Lower Havel Inner Delta near Lake Gülpe, Brandenburg (Germany) - Pohle, Marco; Birnstengel, Susann; Werban, Ulrike (In: Köhler, Anne; Pohle, Marco; Bauckholt, Matteo; Birnstengel, Susann; Kaniecki, Marie; Schneider, Birgit; Werban, Ulrike; Zielhofer, Christoph (2025): Geophysical, Sedimentological and Geochemical Data from the Lower Havel Inner Delta (Gülpe Island), Brandenburg (Germany) [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.983208, 2025)
Electromagnetic induction (EMI) was measured with a CMD-Mini Explorer (GF Instruments s.r.o., Brno, Czech Republic) in June 2024. We used the vertical dipole (VDP) at coil spacings of 0.32 m (VDP1), 0.71 m (VDP2) and 1.18 m (VDP3), archieving effective penetration depths of 0.5 m (VDP1), 1.0 m (VDP2) and 1.8 m (VDP3). According to the manufacturer, 70% of the signal originate from above these depths. The EMI sensors measure the apparent electrical conductivity (ECa, in mS/m). Measurements were taken by carrying the instrument about 0.2 m above ground while being directly connected to D-GPS (Leica GPS1200) for positioning. The acquisition rate was five measurements per second. Data quality was checked by measuring a reference line before and after each measurement. The area investigated by EMI in June 2024 is located southeast of the research station. The survey area there is 8.1 ha in size. The reference line for the measurements there was located in the north-westernmost area of the site. No drift correction had to be applied due to good data quality. Reference lines and single outliers were removed. The data set contains the EMI data with an intercoil spacing of 0.71m.
Keywords: Brandenburg; electromagnetic induction; EMI; floodplain; Lake Gülpe; Near surface geophysics